REVIEW OF REGULATIONS GOVERNING SWITCHING DRUGS FROM RX TO OVER-THE-COUNTER IN THE USA, INDIA, AND EU - G, MEGHANA; SWETHA K, SREE GREESHMA; REDDY J, RAVI KUMAR; RAJU K, VENKATESWARA (Asian Journal of Pharmaceutical and Clinical Research, 2021)
Rx to over-the-counter (OTC) switch is a data-driven, scientifically rigorous, and highly regulated process that allows consumers to have OTC access to a growing range of medicines. Patients often approach a pharmacist instead of a Healthcare Professional for minor illnesses such as fever, aches, nausea, allergies, cough, and cold. Switches are a logical extension for life-cycle management of a product to defense originator company from Generic competitors. The driving factors required for switching are self-diagnosis, self-medication, and self-administration. On increasing of Rx to OTC switching relatively rules and regulations governing are also improving. Label instructions have to be simple and easily understandable by ordinary people by preventing medication errors and drug abuse. Labeling must include indications, warnings, and directions for use especially since they are administered without medical guidance. Adding a graphic description on the label may be useful to patients, mostly illiterate individuals (e.g., Drug Facts Labeling). The advertisement may also influence patients’ decisions on the selection of OTC products. Medicine advertisements should be closely monitored to ensure that they are truthful and are not misleading or unfair. In this respect, it is recommended that advertisements reflect the information that is contained in the product information leaflet, which, in turn, should be unbiased, evidence-based, and presented in a clear, understandable, and easily readable way. This article elaborates on regulatory requirements, challenges, and marketing aspects of Rx to OTC Switching medicinal products.